Vitamin B6, B12, Asam Folat, Tekanan Darah dan Demensia pada Lanjut Usia - Bekti Krisdyana; Diffah Hanim; Sugiarto Sugiarto (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Dementia is a multifactorial disease due to genetic and environmental influences. Lack of intake of vitamins B6, B12, folic acid and blood pressure are one of the environmental factors that cause dementia.Objective: To analyze the relationship between the adequacy of vitamins B6, B12, folic acid and blood pressure with dementia in the elderlyMethod: This research was a cross sectional study, which was carried out in Tulungagung Regency. The sampling technique was cluster random sampling and a sample size of 100 elderly from 7 elderly Posyandu in Tulungagung Regency, with independent variables such as adequacy of vitamin B6, B12, folic acid and blood pressure, while the dependent variable was dementia. Data were analyzed with chi square testResults: Respondents in this study were generally aged 60-74 years (70.0%), women (48.0%), were educated in elementary / junior high school (60.0%) and did not work (69.0%). Most respondents have insufficient vitamin B6, B12 and folic acid in the less category, with percentages of 57.0%, 54% and 64%, respectively. There was an association between the adequacy of vitamins B6, B12 and folic acid with dementia in the elderly (OR=2.302; 95% CI=1.011-5.241; p=0.045; OR=2.397; 95% CI=1.060-5.422; p=0.034; OR=2.516; 95% CI=1.015-6.238; p=0.043). Blood pressure is associated with dementia in the elderly (OR=3.000; 95% CI=1.288-6.988; p=0.010). The average consumption of vitamin B6, B12 and folic acid in the normal group was higher than the dementia group, with a difference of 0.16 ± 0.04 mg, 0.54 ± 0.05 mcg and 65.89 ± 4.95 respectively mcgConclusionABSTRAKLatar Belakang: Demensia merupakan penyakit multifaktorial karena pengaruh genetik dan lingkungan. Minimnya asupan vitamin B6, B12, asam folat dan tekanan darah menjadi salah satu faktor lingkungan yang menyebabkan demensia.Tujuan: Tujuan penelitian ini adalah menganalisis hubungan antara kecukupan vitamin B6, B12, asam folat dan tekanan darah dengan demensia pada lanjut usiaMetode: Penelitian ini berupa penelitian cross sectional, yang dilakukan di Kabupaten Tulungagung. Teknik sampling dengan cluster random sampling dan besar sampel 100 lansia dari 7 posyandu lansia di Kabupaten Tulungagung, dengan variabel bebas berupa kecukupan vitamin B6, B12, asam folat dan tekanan darah, sedangkan variabel terikatnya adalah demensia. Data dianalisis dengan uji chi squareHasil: Responden penelitian ini umumnya berusia 60-74 tahun (70,0 %), wanita (48,0 %), berpendidikan terakhir SD/SMP (60,0 %) dan tidak bekerja (69,0 %). Kebanyakan responden memiliki kecukupan vitamin B6, B12 dan asam folat dalam kategori kurang, dengan persentase masing-masing 57,0 %, 54 % dan 64 %. Ditemukan hubungan antara kecukupan vitamin B6, B12 dan asam folat dengan demensia pada lanjut usia (OR=2,302, 95% CI=1,011-5,241, p=0,045; OR=2,397, 95% CI=1,060-5,422, p=0,034; OR=2,516,95% CI=1,015-6,238, p=0,043). Tekanan darah berhubungan dengan demensia pada lanjut usia (OR=3,000,95% CI=1,288-6,988,p=0,010). Rata-rata konsumsi vitamin B6, B12 dan asam folat kelompok normal lebih tinggi dibandingkan kelompok demensia, dengan selisih masing-masing sebesar 0,16±0,04 mg, 0,54±0,05 mcg dan 65,89 ±4,95 mcg.Kesimpulan: Terdapat hubungan antara kecukupan vitamin B6, B12, asam folat dan tekanan darah dengan demensia pada lanjut usia.